Influence of endwall 2D contouring on endwall adiabatic cooling effectiveness and aerodynamic performance. (July 2019) - Chen, Pingting; Li, Xueying; Ren, Jing; Jiang, Hongde; Simon, Terrence
Highlights: A 2D contoured endwall was designed using aerodynamic optimization system. Thermal and Aero features are compared between the 2D contoured endwall and baseline. Cooling protection is improved on 2D contoured endwall vs. the baseline – same MFR. Cooling effectiveness between two passages scales well with momentum flux ratio. Abstract: Endwall 2D contouring is a presently-employed design method for reducing the strength of secondary flows within gas turbine airfoil passages. Such contouring can lead to significant changes of passage flow. Also affecting passage flow is flow through an interface, or leakage slot, between the combustor and the turbine. Though introduced for eliminating ingression of passage gas into the cavity, leakage flow through the leakage slot, which has bypassed the combustor, can be used to cool the endwall and vane surfaces. Moreover, the leakage flow interacts with the main flow resulting in a change of aerodynamic losses. In this study, a 3D numerical method was used to compare endwall adiabatic cooling effectiveness values, η, and passage Total Pressure Loss Coefficients (TPLC) between a 2D contoured-endwall passage and a flat-endwall passage in a Nozzle Guide Vane (NGV) cascade using several Mass Flow Rate (MFR) values and several momentum flux ratios, I, of slot leakage flow. The numerical method was validated by comparing its computed results with experimental data, then the shape of endwall contouring was designed using an aerodynamic optimization system. The results indicate that with endwall contouring, adiabatic cooling effectiveness values on the endwall are higher than with the flat endwall for all MFR values investigated. Moreover, with the same average momentum flux ratio, I, value of leakage flow, contoured endwall and flat endwall passages show similar adiabatic cooling effectiveness distributions, especially at the regions over the upstream part of the passage, which means that η scales well with I. Over the downstream part of the passage, the contoured endwall cases show higher adiabatic cooling effectiveness values on the contoured endwall with the same average I value as used with the flat endwall passage. Over the MFR range of this study, the contoured-endwall passage shows better aerodynamic performance than that of the flat-endwall passage.